2017
DOI: 10.1007/s12149-017-1217-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of FDG-PET and DWI in breast cancer

Abstract: The preoperative SUV, MTV, and TLG of primary breast cancer are prognostic factors for recurrence, whereas ADC values are not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…DWI, an MRI sequence showing the restricted movement of water molecules in tumoral tissues, was recently introduced as a functional modality to evaluate microstructural characteristics in tumors [ 13 ]. DWI can visualize changes occurring at a cellular spatial scale making it an advantageous tool for evaluating changes in the tumor microenvironment, both before and after NST [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…DWI, an MRI sequence showing the restricted movement of water molecules in tumoral tissues, was recently introduced as a functional modality to evaluate microstructural characteristics in tumors [ 13 ]. DWI can visualize changes occurring at a cellular spatial scale making it an advantageous tool for evaluating changes in the tumor microenvironment, both before and after NST [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging methods, especially mammography, ultrasound and magnetic resonance imaging, play a fundamental role in the diagnosis of BC [2] . Nowadays, also positron emission tomography (PET) is increasingly used in BC [3] , [4] , [5] , [6] , [7] . It has been shown that PET besides detection of distant metastases can also provide additional information about tumor histopathology [5] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the median tumor SUVmax was lower in group 1 than in group 2 patients with cancer (p=0.002). Pretreatment FDG-PET SUV was found to be a prognostic factor for outcome in many types of cancer (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%